ADAPTIVE SYSTEM OF THE BASIC TILLAGE FOR WINTER WHEAT - Kyryliuk, В.; Samets, Н. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The results of the research on the impact of the main production system based on mineral and organo-mineral fertilizers on the yield and quality of wheat grain are presented. The research was conducted during 2009–2021 at a stationary two-factor study field, and included 4 alternative systems of the main substantiation work (shelf, flat, chisel, disk) and two coordination systems: traditional (mineral, background 1) – N60Р60К60 + N30 (feeding) and new (organo-mineral, 2) – white mustard straw + N10/t of straw + N30Р30К30 + N30 (fertilization) in short-rotation 4-joint crop rotation with the following crop growth: soybean, spring barley, white mustard, winter wheat. Soil – chernozem podzolic, medium loam. The content of humus – 2.62–3.12 %, total nitrogen – 0.150–0.163 %, mobile phosphorus – 12.5–19.6 and potassium – 6.5–7.2 mg per 100 g of soil, pH (salt) – 6.0–6.5. Location of plots – systematic. The examined area of the site is 40 m2, the repetition of the study is four times. On the background of mineral fertilizers, the highest yield of wheat (5.67 t/ha) is obtained for a different system of basic tillage. It was found that the use of mineral fertilizer Nitroamophoska in a dose of N60Р60К60 for winter wheat with the organo-mineral fertilizers, where on the background of crop residues of straw straw previously made mineral at a dose of N30Р30К30, was not economically viable. It is noted that on the background of organo-mineral fertilizer (joint use of straw pre-fertilizer and mineral fertilizer N30Р30К30) the highest yield of wheat (5.86 t/ha) was provided by the optimal system of basic tillage based on the depth of 20–22 cm, which can be best adapted for the crop. Under such conditions, a flat system to a depth of 25–27 cm may be acceptable. Particularly high basic quality indicators of winter wheat grain were obtained on the background of mineral fertilizers. On both backgrounds of fertilizers in terms of quality, the advantage was in the shelf system of basic tillage, and in general, in the systems with higher yields there was an improvement in grain quality.